Breastfeeding and asthma outcomes at the age of 6 years: The Generation R Study. Issue 5 (18th May 2016) - den Dekker, Herman T.; Sonnenschein‐van der Voort, Agnes M. M.; Jaddoe, Vincent W. V.; Reiss, Irwin K.; de Jongste, Johan C.; Duijts, Liesbeth
Abstract: Background: Breastfeeding is associated with a lower risk of asthma symptoms in early childhood, but its effect at older ages remains unclear. We examined the associations of duration and exclusiveness of breastfeeding with asthma outcomes in children aged 6 years, and whether these associations were explained by atopic or infectious mechanisms. Methods: We performed a population‐based prospective cohort study among 5675 children. Information about breastfeeding was collected by questionnaires. At age 6 years, we measured interrupter resistance (Rint) and fractional exhaled nitric oxide (FeNO). Information about wheezing patterns (early (≤3 years only), late (>3 years only), persistent (≤3 and >3 years)), and current asthma at 6 years was derived from repeated questionnaires. Results: Compared to children who were ever breastfed, those who were never breastfed had lower FeNO levels (sympercent (95% CI): ‐16.0 (‐24.5, ‐7.5)) and increased risks of late and persistent wheezing (OR(95% CI): 1.69 (1.06, 2.69) and 1.44 (1.00, 2.07), respectively). Shorter duration of breastfeeding was associated with early wheezing and current asthma (1.40 (1.14, 1.73) and 2.19 (1.29, 3.71), respectively). Less exclusive breastfeeding was associated with early wheezing (1.28 (1.08, 1.53)). Breastfeeding duration and exclusiveness were not associated with FeNO or Rint. The associations were not explained by inhalant allergies, partly by lower respiratory tract infections in early life, and to a lesser extent by lower respiratory tract infections in later life. Conclusions: Breastfeeding patterns may influence wheezing and asthma in childhood, which seems to be partly explained by infectious mechanisms. Abstract :